Brain structure correlates of urban upbringing, an environmental risk factor for schizophrenia - Haller, Leila; Lederbogen, Florian; Wüst, Stefan; Deuschle, Michael; Kirsch, Peter; Meyer-Lindenberg, Andreas (Schizophrenia bulletin, 2015)
Urban upbringing has consistently been associated with schizophrenia, but which specific environmental exposures are reflected by this epidemiological observation and how they impact the developing brain to increase risk is largely unknown. On the basis of prior observations of abnormal functional brain processing of social stress in urban-born humans and preclinical evidence for enduring structural brain effects of early social stress, we investigated a possible morphological correlate of urban upbringing in human brain. In a sample of 110 healthy subjects studied with voxel-based morphometry, we detected a strong inverse correlation between early-life urbanicity and gray matter (GM) volume in the right dorsolateral prefrontal cortex (DLPFC, Brodmann area 9). Furthermore, we detected a negative correlation of early-life urbanicity and GM volumes in the perigenual anterior cingulate cortex (pACC) in men only. Previous work has linked volume reductions in the DLPFC to the exposure to psychosocial stress, including stressful experiences in early life. Besides, anatomical and functional alterations of this region have been identified in schizophrenic patients and high-risk populations. Previous data linking functional hyperactivation of pACC during social stress to urban upbringing suggest that the present interaction effect in brain structure might contribute to an increased risk for schizophrenia in males brought up in cities. Taken together, our results suggest a neural mechanism by which early-life urbanicity could impact brain architecture to increase the risk for schizophrenia.